2022
DOI: 10.3390/w14152380
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Modeling Approach to Predict Water Inflow during Karst Tunnel Excavation

Abstract: During tunnel construction in strongly developed karst terrain, water inrush hazards often occur due to the complex hydrogeological conditions, which require accurate prediction of water inflow. In this study, a dynamic modeling approach for water inflow prediction of karst tunnels using the conduit flow process (CFP) is developed that considers both karst duality and changing boundary conditions of the tunnel. The CFP model has a good agreement with field-observed hydraulic head after calibration, and the Nas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The constant total head on the inner circumference of lining h a is applied for Equations ( 10)- (12). For Equation ( 13), zero water pressure on the inner circumference of the lining is used, and A = h 2 − r E 2 .…”
Section: Reference Equation Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The constant total head on the inner circumference of lining h a is applied for Equations ( 10)- (12). For Equation ( 13), zero water pressure on the inner circumference of the lining is used, and A = h 2 − r E 2 .…”
Section: Reference Equation Descriptionmentioning
confidence: 99%
“…Many efforts have been devoted to proposing effective methods to predict water inflow into tunnels over the past few decades. Four kinds of methods, including analytical solutions [8][9][10][11][12][13][14], numerical simulations [15][16][17][18][19], empirical formulas [20,21] and physical experiments [22], have been applied to estimate water inflow into tunnels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies are on the water inflow and water inrush accidents of coal mines, but there are few reports on the water inflow of bauxite mines. The studies of the water inflow in tunnels are also reported [25,26]. Groundwater inflow into Karaj Water Conveyance (KWC) in Northern Iran was estimated using analytical and numerical methods [27].…”
Section: Introductionmentioning
confidence: 99%
“…They used numerical calculations to predict the water inflow situation in the tunnel, providing a reference for corresponding tunnel engineering. Bai et al [22] proposed a tunnel water inflow prediction modeling method based on the pipeline flow process and considering karst bimodality and boundary conditions for tunnel water inflow problems in karst areas, providing some reference for predicting water inflow in karst tunnels. Mahmoodzadeh et al [23] used machine learning algorithms such as LSTM, DNN, KNN, SVR, DT, and GPR combined with hundreds of water inflow data to analyze the performance of LSTM and DNN algorithms in predicting tunnel water inflow.…”
Section: Introductionmentioning
confidence: 99%